Functional analysis of new variants at the low‐density lipoprotein receptor associated with familial hypercholesterolemia. Issue 8 (18th June 2019) - Rodríguez‐Jiménez, Carmen; Pernía, Olga; Mostaza, Jose; Rodríguez‐Antolín, Carlos; de Dios García‐Díaz, Juan; Alonso‐Cerezo, Concepción; García‐Polo, Iluminada; Blanco, Agustín; Lahoz, Carlos; Arrieta, Francisco; Beltrán, Luis; Díaz de Bustamante, Aránzazu; et al.
Abstract: Familial hypercholesterolemia is an autosomal dominant disease of lipid metabolism caused by defects in the genes LDLR, APOB, and PCSK9 . The prevalence of heterozygous familial hypercholesterolemia (HeFH) is estimated between 1/200 and 1/250. Early detection of patients with FH allows initiation of treatment, thus reducing the risk of coronary heart disease. In this study, we performed in vitro characterization of new LDLR variants found in our patients. Genetic analysis was performed by Next Generation Sequencing using a customized panel of 198 genes in DNA samples of 516 subjects with a clinical diagnosis of probable or definitive FH. All new LDLR variants found in our patients were functionally validated in CHO‐ ldlA7 cells. The LDLR activity was measured by flow cytometry and LDLR expression was detected by immunofluorescence. Seven new variants at LDLR were tested: c.518 G>C; p.(Cys173Ser), c.[684 G>T;694 G>T] ;p.[Glu228Asp;Ala232Ser], c.926C>A ;p.(Pro309His), c.1261A>G ;p.(Ser421Gly), c.1594T>A ;p.(Tyr532Asn), and c.2138delC ;p.(Thr713Lysfs*17). We classified all variants as pathogenic except p.(Ser421Gly) and p.(Ala232Ser). The functional in vitro characterization of rare variants at the LDLR is a useful tool to classify the new variants. This approach allows us to confirm the genetic diagnosis of FH, avoiding the classification as "uncertain significant variants", and therefore, carry out cascade family screening. Abstract : Expression of LDLR in the transiently transfected CHO‐ldlA7.